Strategies for real estate brokers to compete in an increasingly technology-driven market: exploring the value of information search and transaction management - Marshall, Justin Garnet (Department of Construction Economics and Management, 2025)
This research examines the evolving role of real estate brokers in South Africa in the context of advancing technology, specifically focusing on Information Search and Transaction Management services. With the traditional information asymmetry enjoyed by brokers being eroded by technological advancements, the study explores how these changes affect the perceived value of brokerage services. Employing a quantitative approach, including a literature review and online surveys targeting consumers and brokers, the study aims to understand the impact of technology on real estate brokerage services and identify effective strategies for brokers to remain competitive in a technology-driven market. The findings indicate a significant evolution in brokerage services, particularly in enhancing information search efficacy, owing to technological integration. The study also reveals that specific elements like negotiation skills and property-client matching significantly contribute to service value. Interestingly, areas like conflict resolution still heavily rely on the broker's human skills, suggesting a balanced need for technological and human elements in brokerage services. The research concludes that successful real estate brokers in a technology-driven market are those who effectively blend technology with their unique human capabilities. The study's implications point to the necessity for continual adaptation and technological integration by brokers, while also emphasizing their irreplaceable human elements. Future research directions include exploring effective technologies in various brokerage service aspects and potential advancements in currently underserved areas like transaction conflict resolution.